Chicana Memoir and the DREAMer Generation: Reyna Grande’s The Distance Between Us as Neo-colonial Critique and Feminist Testimonio - Marion Rohrleitner (Gender a Výzkum)
Reyna Grande’s 2012 memoir The Distance Between Us exemplifies the ongoing influence of the Latin American testimonio on contemporary life writing by immigrants to the United States from the Southern hemisphere, in order to effect social change. Specifically, Grande’s text aims to mobilise readers to facilitate immigration reform for the so-called Dreamers, undocumented immigrants who were brought to the United States as minors. The memoir further showcases how Mexican immigrant writers such as Grande continue genre-blending traditions in Chicana feminist literature in an effort to find an appropriate expression for their complex experiences with migration as gendered, raced, and classed individuals. In doing so, Grande produces a unique form of life writing that is equally inspired by oral narrative, testimonio, autobiography and memoir.